2007
DOI: 10.3171/ped.2007.106.6.490
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous venous drainage preventing safe posterior fossa decompression in patients with Chiari malformation Type I and multisutural craniosynostosis

Abstract: The authors report on two children in whom an anomalous posterior fossa venous drainage pattern prevented safe posterior fossa decompression. Both patients had Chiari malformation Type I, multisutural craniosynostosis, and crowded posterior fossa structures. Both patients had been treated with ventriculoperitoneal shunts for hydrocephalus. Pfeiffer syndrome had been diagnosed in one of the patients, and the other was suspected to have osteogenesis imperfecta. Although both patients were believed to have sympto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…In some cases, preoperative detection of major venous collaterals at the site of a proposed CM decompression may suggest that even bone removal at the foramen magnum is not safe and should not be performed. 1,37 In general, most surgeons agree that CM should not be treated unless it is symptomatic or, in some cases, associated with a spinal syrinx. It is possible that the indications for surgical treatment of CM may be different for individuals with associated craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, preoperative detection of major venous collaterals at the site of a proposed CM decompression may suggest that even bone removal at the foramen magnum is not safe and should not be performed. 1,37 In general, most surgeons agree that CM should not be treated unless it is symptomatic or, in some cases, associated with a spinal syrinx. It is possible that the indications for surgical treatment of CM may be different for individuals with associated craniosynostosis.…”
Section: Discussionmentioning
confidence: 99%
“…Sandberg et al reported on 2 patients with multisutural craniosynostosis, Chiari I malformation, and prior VP shunt placement in whom posterior fossa decompression was avoided due to anomalous venous drainage patterns. 23 Preoperative CT angiography demonstrated hypoplastic jugular foramina and abnormal transosseous venous drainage to the neck and retromastoid region. In addition, Sanchez et al described the onset of facial edema 21 months after correction of BLSS at 2 months of age via strip craniectomy and spring placement; bilateral jugular foraminal stenosis was subsequently identified.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, it is this same patient population that is at most risk of developing anomalous intracranial venous drainage patterns. 1,2,4,10,12,14,19,20,22,23 These intracranial-to-extracranial collateral vessels develop in the occipital region, hindering safe exposure of the posterior calvaria during posterior vault remodeling and Chiari decompression. There are multiple reports in which cranial vault remodeling and Chiari decompression repairs were abandoned due to anomalous venous drainage patterns, either identified through preoperative imaging or intraoperatively.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…19 Along the same lines, separate reports have been published, recommending avoiding surgical intervention because of the perceived risk to the venous system. 15 In an effort to maximize venous drainage, we developed a technique to preserve these outflow tracts by leaving an island of surrounding bone through which anomalous venous channels course, while still decompressing the foramen magnum with this same surgical exposure. It has been our experience that this anatomy is predictable and may be adequately imaged with standard preoperative MRI.…”
Section: Discussionmentioning
confidence: 99%